Hungary : Staff Report for the 2015 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2015)
This 2015 Article IV Consultation highlights that the Hungarian economy is growing at a strong pace helped by accommodative macroeconomic policies and improved market sentiment. Driven by strong domestic demand, output grew by 3.6 percent in 2014. Unemployment declined sharply reflecting the expansion of public works programs and job creation in the private sector. Headline and core inflation decelerated sharply, and inflation expectations fell below the National Bank of Hungary's inflation target. Going forward, output growth is projected to decelerate to 2.75 percent in 2015, on account of a smaller domestic-demand impetus owing to less-supportive fiscal stance and lower investment growth.